CFD Modelling of a Stepped Spillway with Various Step Layouts. (28th November 2019) - Li, Shicheng; Li, Qiulin; Yang, James
Abstract : A traditional stepped spillway is prone to cavitation risks. To improve its hydraulic behaviors, distorted step faces and pool weirs are devised. By numerical modelling, comparative studies are conducted to look into the flow features. The pressures on step surfaces of the unconventional layouts exhibit 3D distributions. Pool weirs are essential in increasing both the min. and max. pressure loads. Pressures on the downstream bed show a unique pattern for V- and inverted V-shaped models, with the extreme pressures at the sidewalls for the former and at the central plane for the latter. Symmetrical secondary flows are formed in V- and inverted V-shaped cases with different patterns. Distributions of turbulent kinetic energy suggest differences in flow motions in all cases. Furthermore, the relative energy loss of flat setups is ∼5.4% lower than that of the pooled ones with the same step face angle; inverting the face angle does not give rise to noticeable change. The results provide reference for relevant projects.